Implementing gender equity in livestock interventions: Caught between patriarchy and paternalism - Tavenner, Katie (International Livestock Research Institute, 2017)
Presented by Katie Tavenner (ILRI/Penn State University), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.